Individualised cognitive functional therapy compared with a combined exercise and pain education class for patients with non-specific chronic low back pain: Study protocol for a multicentre randomised controlled trial - O'Keeffe, M.; Purtill, H.; Kennedy, N.; O'Sullivan, Peter; Dankaerts, W.; Tighe, A.; Allworthy, L.; Dolan, L.; Bargary, N.; O'Sullivan, K. (BMJ Publishing Group, 2015)
Introduction: Non-specific chronic low back pain (NSCLBP) is a very common and costly musculoskeletal disorder associated with a complex interplay of biopsychosocial factors. Cognitive functional therapy (CFT) represents a novel, patientcentred intervention which directly challenges painrelated behaviours in a cognitively integrated, functionally specific and graduated manner. CFT aims to target all biopsychosocial factors that are deemed to be barriers to recovery for an individual patient with NSCLBP. A recent randomised controlled trial (RCT) demonstrated the superiority of individualised CFT for NSCLBP compared to manual therapy combined with exercise. However, several previous RCTs have suggested that class-based interventions are as effective as individualised interventions. Therefore, it is important to examine whether an individualised intervention, such as CFT, demonstrates clinical effectiveness compared to a relatively cheaper exercise and education class. The current study will compare the clinical effectiveness of individualised CFT with a combined exercise and pain education class in people with NSCLBP. Methods and analysis: This study is a multicentre RCT. 214 participants, aged 18-75 years, with NSCLBP for at least 6 months will be randomised to one of two interventions across three sites. The experimental group will receive individualised CFT and the length of the intervention will be varied in a pragmatic manner based on the clinical progression of participants. The control group will attend six classes which will be provided over a period of 6-8 weeks. Participants will be assessed preintervention, postintervention and after 6 and12 months. The primary outcomes will be functional disability and pain intensity. Non-specific predictors, moderators and mediators of outcome will also be analysed. Ethics and dissemination: Ethical approval has been obtained from the Mayo General Hospital Research Ethics Committee (MGH-14-UL). Outcomes will be disseminated through publication according to the SPIRIT statement and will be presented at scientific conferences.